The Operation of the Three Gorges Dam Alters Wetlands in the Middle and Lower Reaches of the Yangtze River - Sun, Gongqi; Lei, Guangchun; Qu, Yi; Zhang, Chengxiang; He, Ke (Frontiers in Environmental Science, 2020)
The operation of the Three Gorges Dam (TGD) has significantly impact on downstream wetland ecosystems. This study applied 3S technology, landscape ecology, and computational models to investigate impact of the TGD on downstream spatial dynamics of floodplains in future. Results revealed the relationship between siltation patterns and wetland types transformation after the operation of the TGD, which are critically important to understand ecological characters dynamics in new environmental setting, and provide science-based conservation and restoration recommendation. After the operation of the TGD, changes between water surface and floodplains areas were spatial heterogeneity. With the increase of distance to the TGD, floodplain erosion force declining gradually. The most important finding is the asymmetric erosion between main river course and its associated floodplain lakes, e.g., Dongting lake.This has significant implications for dam operation in autumn and habitat management. After the operation of the TGD, floodplain in the estuary is driven by both the Yangtze river and ocean currents. The strong hydrological force and reduced sediments of Yangtze river drive erosion of the southern river course in the estuary, whereas, the weakened hydrological force in the northern river course attracts sedimentation.